Vasoactive pharmacologic therapy in cardiogenic shock: a critical review. Issue 1 (15th December 2021) - Kaddoura, Rasha; Elmoheen, Amr; Badawy, Ehab; Eltawagny, Mahmoud F.; Seif, Mohamed A.; Bashir, Khalid; Salam, Amar M.
Abstract: Background: Cardiogenic shock (CS) is an acute complex condition leading to morbidity and mortality. Vasoactive medications, such as vasopressors and inotropes are considered the cornerstone of pharmacological treatment of CS to improve end-organ perfusion by increasing cardiac output (CO) and blood pressure (BP), thus preventing multiorgan failure. Objective: A critical review was conducted to analyze the currently available randomized studies of vasoactive agents in CS to determine the indications of each agent and to critically appraise the methodological quality of the studies. Methods: PubMed database search was conducted to identify randomized controlled trials (RCTs) on vasoactive therapy in CS. After study selection, the internal validity of the selected studies was critically appraised using the three-item Jadad scale. Results: Nine studies randomized 2388 patients with a mean age ranged between 62 and 69 years, were identified. Seven of studies investigated CS in the setting of acute myocardial infarction (AMI). The studies evaluated the comparisons of norepinephrine (NE) vs. dopamine, epinephrine vs. NE, levosimendan vs. dobutamine, enoximone or placebo, and nitric oxide synthase inhibitors (NOSi) vs. placebo. The mean Jadad score of the nine studies was 3.33, with only three studies of a score of 5. Conclusions: The evidence from the studies of vasoactive agents in CS carries uncertainties. The methodological quality between the studies is variable due to the inherent difficulties to conduct a study in CS. Vasopressors and inotropes continue to have a fundamental role given the lack of pharmacological alternatives.